Effects of an Innovative Psychotherapy Program for Surgical Patients: Bridging Intervention in Anesthesiology—A Randomized Controlled Trial. (July 2015) - Kerper, Léonie F.; Spies, Claudia D.; Salz, Anna-Lena; Weiß-Gerlach, Edith; Balzer, Felix; Neumann, Tim; Tafelski, Sascha; Lau, Alexandra; Neuner, Bruno; Romanczuk-Seiferth, Nina; Glaesmer, Heide; Wernecke, Klaus-Dieter; et al.
Abstract : Background: The stepped care program Bridging Intervention in Anesthesiology (BRIA) aims at motivating and supporting surgical patients with comorbid mental disorders to engage in psychosocial mental healthcare options. This study examined the efficacy of BRIA. Methods: This randomized, parallel-group, open-label, controlled trial was conducted in the preoperative anesthesiological assessment clinics and surgical wards of a large university hospital in Germany. A total of 220 surgical patients with comorbid mental disorders were randomized by using the computer-generated lists to one of two intervention groups: BRIA psychotherapy sessions up to 3 months postoperatively (BRIA) versus no psychotherapy/computerized brief written advice (BWA) only. Primary outcome was participation in psychosocial mental healthcare options at month 6. Secondary outcome was change of self-reported general psychological distress (Global Severity Index of the Brief Symptom Inventory) between baseline and month 6. Results: At 6-month follow-up, the rate of patients who engaged in psychosocial mental healthcare options was 30% (33 of 110) in BRIA compared with 11.8% (13 of 110) in BWA ( P = 0.001). Number needed to treat and relative risk reduction were 6 (95% CI, 4 to 13) and 0.21 (0.09 to 0.31), respectively. In BRIA, Global Severity Index decreased between baseline and month 6 ( P < 0.001), whereas it did not change significantly in BWA ( P = 0.197). Conclusions: Among surgical patients with comorbid mental disorders, BRIA results in an increased engagement in subsequent therapy options and a decrease of general psychological distress. These data suggest that it is reasonable to integrate innovative psychotherapy programs into the context of interdisciplinary surgical care. Abstract : In 220 surgical patients with comorbid mental disorders (primarily mood, anxiety and adjustment disorders, or alcohol or tobacco abuse), those randomized to psychotherapy sessions perioperatively and up to 3 months postoperatively were more likely to participate in psychosocial mental health care 6 months after surgery than those randomized to brief written advice only.